CONTRIBUTION OF LEARNING ORIENTATION AND PARENT SOCIO-ECONOMIC STATUS ON THE RESULTS OF SEWING TRAINING PARTICIPANTS IN BALAI LATIHAN KERJA DAN PENGEMBANGAN PRODUKTIVITAS (BLKPP) YOGYAKARTA - Suci Hari Mulyani (Universitas Negeri Yogyakarta, 2019)
Vocational training is an effort to increase productivity and create jobs. In the education process there are factors that influence learning outcomes, including learning orientation and socioeconomic status of parents. This research is a correlational research using survey method with instruments using questionnaires and observation test values. The research subjects used were 31 participants in the skills training program at (BLKPP) Yogyakarta. Data analysis technique uses F test at 5% significance level. The results of the first correlation coefficient are obtained r count = 0.436 R (0.05) (30) = 0.296, so it can be concluded that there is a relationship between learning orientation towards learning outcomes of trainees. The results of the second correlation coefficient obtained r count value (0.574) r table (0.05) (30) (0.296) so that it can be concluded that there is a relationship between the socio-economic status of parents and the learning outcomes of trainees. The results of multiple regression analysis showed that the value of F calculated 7.109 F table (3.32) at a significance level of 5%, so it can be concluded that there is a relationship between learning orientation and socio-economic status of parents on the learning outcomes of skills training participants in BPLKPP Yogyakarta.